2017
DOI: 10.1053/j.gastro.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal Hormone Therapy Is Associated With Increased Risk of Fecal Incontinence in Women After Menopause

Abstract: Background & Aims Low estrogen levels could contribute to development of fecal incontinence (FI) in women after menopause by altering neuromuscular continence mechanisms. However, studies have produced conflicting results on the association between menopausal hormone therapy (MHT) and risk of FI. Methods We studied the association between MHT and risk of FI among 55,828 post-menopausal women (mean age 73 years) who participated in the Nurses’ Health Study, enrolled since 2008, with no report of FI. We define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Staller et al studied the association between HRT and risk of FI among 55.828 postmenopausal women (participating in the WHI, Nurses' Health Study as well as HERS), and current or past use of HRT was associated with a modestly increased risk of FI among postmenopausal women. These results support a potential role for exogenous estrogens in the impairment of the fecal continence mechanism [4,5,33].…”
Section: Influence Of Hrt On Fisupporting
confidence: 76%
“…Staller et al studied the association between HRT and risk of FI among 55.828 postmenopausal women (participating in the WHI, Nurses' Health Study as well as HERS), and current or past use of HRT was associated with a modestly increased risk of FI among postmenopausal women. These results support a potential role for exogenous estrogens in the impairment of the fecal continence mechanism [4,5,33].…”
Section: Influence Of Hrt On Fisupporting
confidence: 76%
“…Since bowel disturbances may impact the relationship between physical activity and FI, we conducted separate analyses examining the association of physical activity with risk of liquid or solid stool FI alone. Covariates were selected a priori based on previously reported risk factors for FI 1 , 2 , 4 , 17 . BMI, MHT use, smoking, and diagnoses of diabetes mellitus, hypertension, or neurologic disease were included as time-varying covariates to account for changes in these exposures over time.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, estrogen taken as part of menopausal replacement therapy (MRT) has been shown to be associated with increased FI symptoms in women. [4] In the Nurses’ Health Study, the authors reported that women who had used MRT in the past had an increased hazard ratio for FI of 1.32 (95% CI, 1.20-1.45) compared to women who had never used MRT. [4] Women who took oral combined estrogen and progestin MRT also had an increased risk of FI (hazard ratio, 1.37; 95% CI, 1.10-1.70) compared to women who used estrogen-only MRT.…”
Section: Discussionmentioning
confidence: 99%
“…[4] In the Nurses’ Health Study, the authors reported that women who had used MRT in the past had an increased hazard ratio for FI of 1.32 (95% CI, 1.20-1.45) compared to women who had never used MRT. [4] Women who took oral combined estrogen and progestin MRT also had an increased risk of FI (hazard ratio, 1.37; 95% CI, 1.10-1.70) compared to women who used estrogen-only MRT. [4] Of note, in the current study, women who reported FI symptoms reported higher rates of “ever” using hormones compared to women without FI symptoms.…”
Section: Discussionmentioning
confidence: 99%